Comparison and complementary use of in situ and remote sensing aerosol measurements in the Athens Metropolitan Area. (1st May 2020) - Vratolis, S.; Fetfatzis, P.; Argyrouli, A.; Soupiona, O.; Mylonaki, M.; Maroufidis, J.; Kalogridis, A.-C.; Manousakas, M.; Bezantakos, S.; Binietoglou, I.; Labzovskii, L.D.; Solomos, S.; et al.
Abstract: In the summer of 2014 in situ and remote sensing instruments were deployed in Athens, in order to study the concentration, physical properties, and chemical composition of aerosols. In this manuscript we aim to combine the measurements of collocated in situ and remote sensing instruments by comparison and complementary use, in order to increase the accuracy of predictions concerning climate change and human health. We also develop a new method in order to select days when a direct comparison on in situ and remote sensing instruments is possible. On selected days that displayed significant turbulence up to approximately 1000 m above ground level (agl), we acquired the aerosol extinction or scattering coefficient by in situ instruments using three approaches. In the first approach the aerosol extinction coefficient was acquired by adding a Nephelometer scattering coefficient in ambient conditions and an Aethalometer absorption coefficient. The correlation between the in situ and remote sensing instruments was good (coefficient of determination R 2 equal to 0.69). In the second approach we acquired the aerosol refractive index by fitting dry Nephelometer and Aethalometer measurements with Mie algorithm calculations of the scattering and absorption coefficients for the size distribution up to a maximum diameter of 1000 nm obtained by in situ instruments. The correlation in this case was relatively good ( R 2 equal to 0.56). Our next step was to compare the extinction coefficient acquired by remote sensing instruments to the scattering coefficient calculated by Mie algorithm using the size distribution up to a maximum diameter of 1000 nm and the equivalent refractive index ( E R I C O R ), which is acquired by the comparison of the size distributions obtained by a Scanning Mobility Particle Sizer (SMPS) and an Optical Particle Counter (OPC). The agreement between the in situ and remote sensing instruments in this case was not satisfactory ( R 2 equal to 0.35). The last comparison for the selected days was between the aerosol extinction Ångström exponent acquired by in situ and remote sensing instruments. The correlation was not satisfactory ( R 2 equal to 0.4), probably due to differences in the number size distributions present in the air volumes measured by in situ and remote sensing instruments. We also present a day that a Saharan dust event occurred in Athens in order to demonstrate the information we obtain through the synergy of in situ and remote sensing instruments on how regional aerosol is added to local aerosol, especially during pollution events due to long range transport. Graphical abstract: Highlights: Comparison and complementary use of in situ and remote sensing instruments. A new method to determine days when in situ-remote comparison is possible. Good correlation between in situ-remote sensing aerosol extinction coefficient. Vertical mixing of locally produced and transported aerosol is demonstrated.